2018
DOI: 10.4028/www.scientific.net/amm.882.64
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Aspects of Current Market Developments, Different Product Types and Innovative Manufacturing Processes of Electric Motors

Abstract: There are numerous levers and constraints affecting the sustainability of electric motors. While previous work mostly focuses on individual energy and resource efficiency potentials within single phases of the motor’s lifecycle, this paper summarizes sustainability aspects from three different perspectives, namely from the market, product and process view. The first part of this paper analyzes the electric motor market to emphasize the significance of this industry and to outline the importance of state-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The sustainability of electric motors encompasses their entire lifecycle, from production to end-of-life management. Mayr et al (2018) highlight the importance of considering the market, product, and process perspectives in assessing the sustainability of electric motors. This includes state-regulated efficiency classes, the range of motor types and their sustainability characteristics, and the energy and resource efficiency of manufacturing processes.…”
Section: Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The sustainability of electric motors encompasses their entire lifecycle, from production to end-of-life management. Mayr et al (2018) highlight the importance of considering the market, product, and process perspectives in assessing the sustainability of electric motors. This includes state-regulated efficiency classes, the range of motor types and their sustainability characteristics, and the energy and resource efficiency of manufacturing processes.…”
Section: Sustainabilitymentioning
confidence: 99%
“…This approach is crucial in meeting the increasing demand for electric traction systems and enhancing the economical relevance of production processes (Peter et al, 2013). Mayr et al (2018) provided a comprehensive overview of the sustainability aspects of electric motors from market, product, and process perspectives. The study analyzed the electric motor market, emphasizing the significance of stateregulated efficiency classes.…”
Section: Innovations In Sustainable Materials and Manufacturing Proce...mentioning
confidence: 99%
“…The PWM value is then used to rotate the DC motor, so that the lift will reach the desired speed and height. It was found that the tool can control the speed and position of the elevator, only that there is still an error in the position control system made [22].…”
Section: Proportional Integral Derivatives (Pid)mentioning
confidence: 99%
“…A discussion of various types of electric motors from a sustainability point of view is presented in [18]. Common circular economy strategies for electric motors, as discussed in [19], are reuse, refurbish, remanufacture and recycle.…”
Section: Common Circular Economy Strategies For Electric Motors and Impactsmentioning
confidence: 99%
“…Recently, Bonfante et al [24] have presented a review of the sustainability aspects (including economic aspects, social impacts and environmental impacts) for rare earth materials used in electric motors. The environmental footprints during the mining process of rare earth materials have been discussed in [25] and on energy consumption during the production process [18].…”
Section: Common Circular Economy Strategies For Electric Motors and Impactsmentioning
confidence: 99%